AN ANALYSIS ON THE VIOLATION OF COOPERATIVE PRINCIPLES IN THE FILM AVENGERS - Deyana Nika Wildan; Sari Rejeki; M Taufik (Universitas Pakuan, 2020)
This research is an analysis on the violation of cooperative principles in the movie Avengers that also describes the type of violation of cooperative principle contained in every conversation in the movie. The research is conducted by using descriptive qualitative method. The subject of this research is the conversation that occurs in the movie Avengers, whilst the object of this research is the data containing forms of every conversation violations of the cooperative principle in the movie Avengers. The technique used in collecting data is called note technique. The data obtained is classified based on the form of violation of cooperative principles. The result of the research shows that the form of violation of the cooperative principle that occurs in the Avengers movie consists of four maxims: the maxim of quantity, the maxim of quality, the maxim of relevance, and the maxim of manner. The violation on the maxim of cooperation occurs because of the same knowledge held by the speech participants and the speech partners in discussing a problem, clarifying information, and changing the subject.Keywords: Violations of cooperative principles, maxim, movie, avengers.